2012
DOI: 10.1371/journal.pone.0031430
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Novel Collagenase (XIAFLEX®) on Dupuytren's Disease Fibroblasts Displays Unique Drug Related Properties

Abstract: Dupuytren's disease (DD) is a benign, fibroproliferative disease of the palmar fascia, with excessive extracellular matrix (ECM) deposition and over-production of cytokines and growth factors, resulting in digital fixed flexion contractures limiting hand function and patient quality of life. Surgical fasciectomy is the gold standard treatment but is invasive and has associated morbidity without limiting disease recurrence. Injectable Collagenase Clostridium histolyticum (CCH) - Xiaflex® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 76 publications
(91 reference statements)
0
46
1
Order By: Relevance
“…RNA extraction was performed using RNeasy mini kit (Qiagen, Crawley, UK). 15 Subsequently, 1 mg mRNA was converted to cDNA using qScript cDNA Synthesis kit (Quanta BioSciences, Gaithersburg, MD, USA) 15 Real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) was carried out with standard protocol 15 using a number of gene-specific primers (Supplementary Table S3). …”
Section: Immunofluorescencementioning
confidence: 99%
“…RNA extraction was performed using RNeasy mini kit (Qiagen, Crawley, UK). 15 Subsequently, 1 mg mRNA was converted to cDNA using qScript cDNA Synthesis kit (Quanta BioSciences, Gaithersburg, MD, USA) 15 Real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) was carried out with standard protocol 15 using a number of gene-specific primers (Supplementary Table S3). …”
Section: Immunofluorescencementioning
confidence: 99%
“…Collagenase isolated from Clostridium histolyticum was clinically proven for treatment of Depuytren's disease. 18 It acts as a collagenolytic enzyme, which digests triple-helical collagens into small peptides. Since the collagenase contains both type I and II, it is also applicable to digest the extracellular matrix of articular cartilage, which has mainly type II collagen.…”
Section: Introductionmentioning
confidence: 99%
“…Injectible collagenase is more efficient than surgical fasciotomy and has milder side effects, which leads to higher patient satisfaction [97,98]. Studies on the influence of CHCs on Dupuytren's cords and on Dupuytren's disease fibroblasts have demonstrated that clostridial collagenases can efficiently digest ECM of Dupuytren's disease cords without inducing significant cytotoxicity or structural damage to non-collagenous tissue elements [99,100]. In the last decade translational research has introduced the non-surgical technique of enzymatic fasciotomy with collagenase injections and able to increase quality of life [96,101].…”
Section: Collagenase As Debriding Agent In Wound Healingmentioning
confidence: 99%